Effect of patterned electrospun hierarchical structures on alignment and differentiation of mesenchymal stem cells: Biomimicking bone. (11th February 2018) - Sankar, Sharanya; Kakunuri, Manohar; D. Eswaramoorthy, Sindhuja; Sharma, Chandra S.; Rath, Subha N.
Abstract: Considering the complex hierarchical structure of bone, biomimicking the micro and nano level features should be an integral part of scaffold fabrication for successful bone regeneration. We aim to biomimic the microstructure and nanostructure of bone and study the effect of physical cues on cell alignment, proliferation, and differentiation. To achieve this, we have divided the scaffolds into groups: electrospun SU‐8 nanofibers, electrospun SU‐8 nanofibers with UV treatment, and micropatterned (20 μm sized ridges and grooves) SU‐8 nanofibers by photolithography with UV treatment. Two types of culture conditions were applied: with and without osteoinduction medium. In vitro cell proliferation assays, protein estimation, alkaline phosphatase osteodifferentiation assay, live dead assay, and cell alignment studies were performed on these micropatterned nanofiber domains. Our findings show that patterned surface induced an early osteodifferentiation of mesenchymal stem cells even in absence of osteoinduction medium. An interesting similarity with the helicoidal plywood model of the bone was observed. The cells showed layering and rotation along the patterns with time. This resembles the in vivo anisotropic multilamellar bone tissue architecture thus, closely mimicking the subcellular features of bone. This might serve as a smart biomaterial surface for mesenchymal stem cell differentiation in therapeutics where the addition of external chemical factors is a challenge.